Pleiotropic Effects of Cell Wall Amidase LytA on Streptococcus pneumoniae Sensitivity to the Host Immune Response - Ramos-Sevillano, Elisa (Infect Immun, 2015)
The complement system is a key component of the host immune response for the recognition and clearance of Streptococcus pneumoniae. In this study, we demonstrate that the amidase LytA, the main pneumococcal autolysin, inhibits complement-mediated immunity independently of effects on pneumolysin by a complex process of impaired complement activation, increased binding of complement regulators, and direct degradation of complement C3. The use of human sera depleted of either C1q or factor B confirmed that LytA prevented activation of both the classical and alternative pathways, whereas pneumolysin inhibited only the classical pathway. LytA prevented binding of C1q and the acute-phase protein C-reactive protein to S. pneumoniae, thereby reducing activation of the classical pathway on the bacterial surface. In addition, LytA increased recruitment of the complement downregulators C4BP and factor H to the pneumococcal cell wall and directly cleaved C3b and iC3b to generate degradation products. As a consequence, C3b deposition and phagocytosis increased in the absence of LytA and were markedly enhanced for the lytA ply double mutant, confirming that a combination of LytA and Ply is essential for the establishment of pneumococcal pneumonia and sepsis in a murine model of infection. These data demonstrate that LytA has pleiotropic effects on complement activation, a finding which, in combination with the effects of pneumolysin on complement to assist with pneumococcal complement evasion, confirms a major role of both proteins for the full virulence of the microorganism during septicemia.